2009
DOI: 10.1007/s11524-009-9415-y
|View full text |Cite
|
Sign up to set email alerts
|

Digital Divide: Variation in Internet and Cellular Phone Use among Women Attending an Urban Sexually Transmitted Infections Clinic

Abstract: We sought to describe: (1) the prevalence of internet, cellular phone, and text message use among women attending an urban sexually transmitted infections (STI) clinic, (2) the acceptability of health advice by each mode of information and communication technology (ICT), and (3) demographic characteristics associated with ICT use. This study is a cross-sectional survey of 200 English-speaking women presenting to a Baltimore City STI clinic with STI complaints. Participants completed a self-administered survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 17 publications
(17 reference statements)
4
36
1
Order By: Relevance
“…15 However, a 2008 study of primarily African-American women attending an urban sexually transmitted infection clinic reported very high rates of cell phone ownership (93%) and text messaging (79%). 4 Our data confirm that the demographic reach of cell phones has expanded, and further we found that minority groups (African-Americans and Hispanics) surveyed were more amenable to receiving information from healthcare providers via text messaging than White patients. There are some drawbacks to using text messaging for healthcare-related communication.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…15 However, a 2008 study of primarily African-American women attending an urban sexually transmitted infection clinic reported very high rates of cell phone ownership (93%) and text messaging (79%). 4 Our data confirm that the demographic reach of cell phones has expanded, and further we found that minority groups (African-Americans and Hispanics) surveyed were more amenable to receiving information from healthcare providers via text messaging than White patients. There are some drawbacks to using text messaging for healthcare-related communication.…”
Section: Discussionsupporting
confidence: 83%
“…3 In one study of women attending an urban sexually transmitted infections clinic, 93% reported owning a cellular phone and 79% used text messaging to communicate. 4 Not surprisingly, text messaging is an increasingly common method of communicating between medical providers and patients. Text message reminders of clinic appointments are being used in a number of healthcare settings.…”
mentioning
confidence: 99%
“…This can be explained in terms of the 'digital divide,' since health-seeking behavior using the internet seems to be related to the general internet activities of epilepsy patients [37]. In previous studies, there were major differences between online and offline health seekers in terms of age, income, and education [42][43][44]. However, only higher education differed between the two groups in our sample, while age and income did not.…”
Section: Discussionmentioning
confidence: 49%
“…7 These findings run contrary to reports concerning Internet use among lower socioeconomic groups and ethnic minorities published only a few years ago, mitigating concerns that expanding the use of electronic communication between patients and providers would widen healthcare disparities. The majority of caregivers have access to one or both of these technologies, and a significant number want to be able to use e-mail or text messaging to communicate with their provider.…”
Section: Discussionmentioning
confidence: 84%